The Reform of the European Union Budget: what do we Seek? - Galinienė, Birutė; Dikovič, Olga (Ekonomika, 2008)
The importance of financial flows to and from the EU budget is widely recognized because contributions to the EU budget and payments from it undoubtedly influence not only the expenditures and revenues of the national budget, but also the priorities of national policy and the whole economy of the country. But the level of the EU financial assistance depends mainly on the EU budget structure: its size, main budget financing principles and the priorities Europe has chosen. The structure of the current EU budget was formed in 1987, when the European Commission submitted its different proposals on every category of the EU budget expenditure and its own resources system. Twenty years passed, and Europe has changed dramatically: the number of EU member states increased from 12 to 27, new priorities as well as new problems that which can be solved at the EU level only have appeared. Therefore Europe’s policies and their financing need to evolve new priorities. The first public step in the process of the reform of all aspects of EU spending and resources was made in September 2007 by the European Commission through the publication of the Consultation paper on the EU budget reform, The aim of this consultation is to determine the structure and direction of the European Union’s spending priorities to meet the challenges of the globalized world in the next decade and beyond.The present EU budget comprises five headings which seem to fully correspond to the priorities of modem Europe because it reflects the main and most up-ta-date European policies. However, facts show that the EU budget is a historical relic because the biggest part of the EU expenditure goes on supporting the agricultural sector whose economic significance is declining and therefore it cannot contribute to growth in Europe. Moreover, the major part of the EU structural funds is allocated to high income countries and makes it impossible for lowincome countries to catch up with the rest. Therefore, the EU claim to become a modem, dynamic and competitive knowledge economy requires to review its budget priorities and structure to finance first those economic and social areas where it is best able to make a contribution to the growth and solidarity in Europe.The European Commission started the EU budget review process with the Consultation paper which invited all actors at all levels to participate in a frank debate on future challenges and to decide how the EU spending can be focused on where it can generate the highest benefit Member states participating in these debates have a perfect opportunity to rethink and distinguish new national priorities. In the process of discussion in Lithuania, it is also important to combine national and European interests as well as to reach an agreement internally: to combine sectoral and national interests and to find a balance between different actors participating in this discussion.In the course of discussion on the EU budget review, it is vital to remember that a higher level of financing does not necessarily ensures better results on the EU level. It is also important to decide whether it is easier to achieve the EU goals by increasing the level of financing or by intensifying the control or improving the regulation. Its is even more import ant to find a reasonable balance between the volume of financing and the European value added.